Synthesis and evaluation of nanoglobule-cystamine-(Gd-DO3A), a biodegradable nanosized magnetic resonance contrast agent for dynamic contrast-enhanced magnetic resonance urography - Rongzuo Xu (Dove Medical Press, 2010)
Rongzuo Xu1, Todd Lyle Kaneshiro1, Eun-Kee Jeong2, Dennis L Parker2, Zheng-Rong Lu31Department of Pharmaceutics and Pharmaceutical Chemistry, University of Utah, Salt Lake City, UT, USA; 2Department of Radiology, University of Utah, Salt Lake City, UT, USA; 3Department of Biomedical Engineering, Case Western Reserve University, Cleveland, OH, USAAbstract: Dynamic contrast-enhanced magnetic resonance imaging has been recently shown to be effective for diagnostic urography. High-resolution urographic images can be acquired with T1 contrast agents for the kidney and urinary tract with minimal noise in the abdomen. Currently, clinical contrast agents are low molecular weight agents and can rapidly extravasate from blood circulation, leading to slow contrast agent elimination through kidney and consequently providing limited contrast enhancement in urinary tract. In this study, a new biodegradable macromolecular contrast agent, nanoglobule-G4-cystamine-(Gd-DO3A), was prepared by conjugating Gd-DO3A chelates on the surface of a generation 4 nanoglobule, poly-l-lysine octa(3-aminopropyl)silsesquioxane dendrimer, via a disulfide spacer, where the carrier had a precisely defined nanosize that is far smaller than the renal filtration threshold. The in vivo contrast enhancement and dynamic imaging of the urinary tract of the agent was evaluated in nude mice using a low molecular weight agent Gd(DTPA-BMA) as a control. The agent eliminated rapidly from blood circulation and accumulated more abundantly in urinary tract than Gd(DTPA-BMA). The fast elimination kinetics is ideal for functional evaluation of the kidneys. The morphology of the kidneys and urinary tract was better visualized by the biodegradable nanoglobular contrast agent than Gd(DTPA-BMA). The agent also resulted in low liver contrast enhancement, indicating low nonspecific tissue deposition. These features render the G4 nanoglobule-cystamine-(Gd-DO3A) conjugate a promising contrast agent for magnetic resonance urography.Keywords: dendrimer, gadolinium(III) contrast agent, disulfide bond, nanoparticle